2003
DOI: 10.1124/mol.63.5.983
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Binding of Peroxisome Proliferator-Activated Receptor γ by Synthetic Cannabinoid Ajulemic Acid

Abstract: Ajulemic acid (AJA) is a synthetic analog of the tetrahydrocannabinol (THC) metabolite THC-11-oic acid; THC is a major active ingredient of the drug marijuana derived from the plant cannabis. AJA has potent analgesic and anti-inflammatory activity without the psychotropic action of THC. Unlike the nonsteroidal anti-inflammatory drugs, AJA is not ulcerogenic at therapeutic doses, making it a promising anti-inflammatory drug. However, the mechanism of AJA action remains unknown. Here we report that AJA binds dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 48 publications
2
89
1
1
Order By: Relevance
“…We have shown [Liu et al, 2003] that AjA activates PPARg in HEK293 cells, and we have observed the same effect of AjA in human FLS (unpublished). PPARs were first cloned as nuclear receptors that mediate the effects on gene transcription of synthetic compounds called peroxisome proliferators.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We have shown [Liu et al, 2003] that AjA activates PPARg in HEK293 cells, and we have observed the same effect of AjA in human FLS (unpublished). PPARs were first cloned as nuclear receptors that mediate the effects on gene transcription of synthetic compounds called peroxisome proliferators.…”
Section: Discussionsupporting
confidence: 67%
“…AjA binds to and activates the nuclear receptor peroxisome proliferator activated receptor gamma (PPARg) in vitro [Liu et al, 2003]. Therefore, we investigated the influence of AjA on release of MMPs from stimulated human FLS and mouse embryonic fibroblasts (MEF), and we examined the role of PPARg in the mechanism of action of AjA.…”
mentioning
confidence: 99%
“…These remarkable results are potentially important in light of accumulating evidence that the timing of COX-2 expression may determine its potential to promote either induction or resolution of inflammation by regulating the production of prostaglandins, depending on the stage and progression of the inflammatory response (Willoughby et al, 2000). Although an earlier report suggests a mechanism for AJA involving PPAR-g (Liu et al, 2003), a more recent study shows that this is not always the case (Johnson et al, 2007) so that AJA may act by either PPAR-g dependent or independent mechanisms.…”
Section: Ajulemic Acid (Aja)mentioning
confidence: 94%
“…13,44 Indeed, PPAR␥ agonists ameliorate experimental colitis, [45][46][47] and PPAR␥ expression is reduced in patients with ulcerative colitis. 20 To verify whether PPAR␥ was also involved in colitis improvement after BCP treatment, the PPAR␥ antagonist GW9662 (1 mg/kg, i.p.)…”
Section: Beneficial Effects Of ␤-Caryophyllene On Dss-induced Colitismentioning
confidence: 99%
“…13,14 PPAR␥ is a member of the superfamily of nuclear receptors and has important anti-inflammatory activity, 15,16 because it inhibits the activation of nuclear factor B (NF B) and the expression of the proinflammatory cytokines IL-1␤ and tumor necrosis factor-␣ (TNF-␣). [17][18][19] The colon expresses a high density of PPAR␥, 20,21 and much evidence points to the involvement of the PPAR␥ receptor in the regulation of intestinal inflammation.…”
mentioning
confidence: 99%